Subtitling Strategies of Swear Words in Deadpool One & Deadpool Two Film - Rohmawati Rohmawati (Indonesian Journal of EFL and Linguistics, 2021)
Subtitles has always been seen as a savior by a lot of people because it breaks all language barriers and made various films and series to be more understandable and watchable. However, the act of subtitling is not as easy as other people think. There are so many restraints in subtitling. One of those restrains is cultural differences in translating swear words. This research aims to obtain data concerning the subtitling strategies of swear words that are found in the subtitles of Deadpool One and Deadpool Two films. The descriptive qualitative method is employed because this research relies on the data obtained from subtitles, which are non-numerical data, and the data analysis will be served descriptively. The results of this research show that according to Gottlieb's (1992) theory, the subtitlers for Deadpool One and Deadpool Two used six different subtitling strategies in each film. The subtitler in Deadpool One tends to use the paraphrase and deletion strategies, followed by condensation, decimation, and transfer, with expansion being the least employed. The subtitler in Deadpool Two, on the other hand, employs deletion as the most used strategy. The subtitler's next most used strategies are paraphrase, condensation, decimation, and transfer; the least commonly employed strategy is expansion.